Neuron-Specific Deletion of Scrib in Mice Leads to Neuroanatomical and Locomotor Deficits - Ezan, Jerome; Moreau, Maité M.; Mamo, Tamrat M.; Shimbo, Miki; Decroo, Maureen; Sans, Nathalie; Montcouquiol, Mireille (Frontiers in Genetics, 2022)
Scribble (Scrib) is a conserved polarity protein acting as a scaffold involved in multiple cellular and developmental processes. Recent evidence from our group indicates that Scrib is also essential for brain development as early global deletion of Scrib in the dorsal telencephalon induced cortical thickness reduction (microcephaly) and alteration of interhemispheric connectivity (corpus callosum and hippocampal commissure agenesis). In addition, Scrib conditional knock-out (cKO) mice have behavioral deficits such as locomotor activity impairment and memory alterations. Given Scrib broad expression in multiple cell types in the brain, we decided to determine the neuronal contribution of Scrib for these phenotypes. In this study, we sought to further investigate the function of Scrib specifically in excitatory neurons on the formation of forebrain cortical structures and the regulation of locomotor behavior. To do so, we generated a novel neuronal glutamatergic specific Scrib cKO mouse line called Nex-Scrib-/- cKO. Remarkably, cortical layering and commissures were impaired in these mice and reproduced to some extent the previously described phenotype in global Scrib cKO. In addition, and in contrast to our previous results using Emx1-Scrib-/- cKO, the Nex-Scrib-/- cKO mutant mice exhibited significantly reduced locomotion. These findings refine our previous results and highlight a cell-autonomous role for Scrib in neuronal migration during corticogenesis and on commissure formation. Using locomotor behavior assays, we found that neuronal Scrib contributes to a proper locomotion. Altogether, the novel cKO model described in this study further highlight an essential role for Scrib in forebrain development and locomotor behavior.